The information revolution, social issues and the expansion of assistance in Uruguay at the beginning of the 21st century - Mariatti Acosta, Alejandro Gabriel (2022)
This article analyses the policy of family allowance (cash transfers) in Uruguay. This mechanism first appeared in 1943; in 2005, during the Frente Amplio government, the use of new technologies brought adjustments to this policy and its original principles. This paper studies how technological improvements and the use of the Critical Deprivation Index (CCI) —whose purpose is to select households in a situation of socioeconomic vulnerability that receives family allowances— have modified the Uruguayan public administration, labour relations and the organization of work. The methodology reviewed laws from 1943, 2005, and 2007 and supporting secondary sources provided evidence on profiling changes and the course of allocations. Arguably the incorporation of technologies depoliticizes poverty because monitoring and supervision of allowances correspond to the agent overseeing the software operation and the collection of data.